2014
DOI: 10.1021/jf404826u
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flavonoids and Hydroxycinnamic Acid Derivatives in Rapeseeds (Brassica napus L. var. napus) by HPLC-PDA–ESI(−)-MSn/HRMS

Abstract: A comprehensive description of flavonoids and hydroxycinnamic acid derivatives in Brassica napus L. var. napus seeds is important to improve rapeseed quality. HPLC-PDA-ESI(-)-MS(n)/HRMS has been broadly applied to study phenolic compounds in plants. In the present study, crude phenolic compounds extracted from rapeseed were subjected to column chromatography, alkaline hydrolysis, and HPLC-PDA-ESI(-)-MS(n)/HRMS analysis. A total of 91 flavonoids and hydroxycinnamic acid derivatives were detected, including 39 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 36 publications
4
53
0
1
Order By: Relevance
“…3C). Phenolic compounds such as flavonols and cinnamic acid ester derivatives (Lin et al, 2011;Shao et al, 2014) increased in all treatments.…”
Section: Metabolome Responsesmentioning
confidence: 96%
“…3C). Phenolic compounds such as flavonols and cinnamic acid ester derivatives (Lin et al, 2011;Shao et al, 2014) increased in all treatments.…”
Section: Metabolome Responsesmentioning
confidence: 96%
“…Under optimized separation conditions (see Section 2), four “unknown” compounds could be collected (“unknowns” 1 , 2 , 3 and 4 ) and identified by UHPLC‐Q‐TOF. The structural information, given in Supporting Information Table S2, was found to be relevant according the literature . These four compounds were finally identified as 1,6‐disinapoylglucoside ( 1 ), sinapoylglycoside ( 2 ), disinapoylgentiobiose ( 3 ) and sinapoylgentiobiose ( 4 ), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Flavonoids, especially anthocyanins, as the main pigments in flowers are responsible for colour variations (Jaakola, ). Hence, we extracted total polyphenols from petals of S2 hybrids and parents to quantify total soluble phenolic and flavonoid content (Shao et al, ). We found that the total phenolic content was more accumulated in B. rapa than B. oleracea and hybrid progeny (Figure ), agreeing to the morphological observation.…”
Section: Resultsmentioning
confidence: 99%